A Comparison of Mainstream Genotyping Platforms for the Evaluation and Use of Barley Genetic Resources - Darrier, Benoit; Russell, Joanne; Milner, Sara G.; Hedley, Pete E.; Shaw, Paul D.; Macaulay, Malcolm; Ramsay, Luke D.; Halpin, Claire; Mascher, Martin; Fleury, Delphine L.; Langridge, Peter; Stein, Nils; et al. (Frontiers in Plant Science, 2019)
We compared the performance of two commonly used genotyping platforms, Genotyping-by-Sequencing (GBS) and Single Nucleotide Polymorphism-Arrays (SNP), to investigate the extent and pattern of genetic variation within a collection of 1,000 diverse barley genotypes selected from the German Federal ex situ genebank hosted at IPK Gatersleben. Each platform revealed equivalent numbers of robust bi-allelic SNPs (39,733 and 37,930 SNPs for the 50K SNP-array and GBS datasets respectively). A small overlap of 464 SNPs was common to both platforms, indicating that the methodologies we used selectively access informative polymorphism in different portions of the barley genome. Approximately half of the GBS dataset was comprised of SNPs with Minimal Allele Frequencies (MAF) below 1%, illustrating the power of GBS to detect rare alleles in diverse germplasm collections. While desired for certain applications, the highly robust calling of alleles at the same SNPs across multiple populations is an advantage of the SNP-array, allowing direct comparisons of data from related or unrelated studies. Overall MAFs and diversity statistics were higher for the SNP-array data, potentially reflecting the conscious removal of markers with a low MAF in the ascertainment population. A comparison of similarity matrices revealed a positive correlation between both approaches, supporting the validity of using either for genebank characterization. To explore the potential of each dataset for focused genetic analyses we explored the outcomes of their use in genome-wide association scans (GWAS) for row type, growth habit and non-adhering hull, and discriminant analysis of principle components (DAPC) for the drivers of sub-population differentiation. Interpretation of the results from both types of analysis yielded broadly similar conclusions indicating that choice of platform used for such analyses should be determined by the research question being asked, group preferences and their capabilities to extract and interpret the different types of output data easily and quickly. Access to the requisite infrastructure for running, processing, analyzing, querying, storing and displaying either datatype is an additional consideration. Our investigations reveal that for barley the cost per genotyping assay is less for SNP-arrays than GBS, which translates to a cost per informative datapoint being significantly lower for the SNP-array.